Psychometric properties of the Teacher beliefs of environmental education questionnaire. Issue 2 (3rd April 2019) - Mullens, Ashley W.; Cater, Melissa
ABSTRACT: This study describes the development and initial validation of a tool to measure teachers' beliefs about environmental education (EE), beliefs about their own self-efficacy in teaching EE in their classroom, beliefs about the support they receive to teach EE in their classroom, motivators of their decision to teach EE in their classroom, and concerns related to teaching EE in their classroom. Survey respondents (N = 620) were 21–74 years of age. The majority of respondents were female, and most of them taught science than any other subject. Exploratory factor analysis was used to examine the internal structure of the instrument. The cumulative percentage of variance explained by the constructs was approximately 63%, and reliability estimates were 0.857 and above.